Thermal Conductivity of Ti-6Al-4V in Laser Powder Bed Fusion - Bartsch, Katharina; Bossen, Bastian; Chaudhary, Waqar; Landry, Michael; Herzog, Dirk (Frontiers in Mechanical Engineering, 2022)
With increasing maturity of the laser powder bed fusion (PBF-LB/M) process, the related products are becoming more complex. The more conventional parts are integrated into one design, the more requirements regarding local material properties arise. This concerns e.g. products with high demands regarding temperature management. Here, different thermal conductivities within the part enable the control of the temperature distribution as well as the direction of heat flows. The realization of those local properties poses a challenge, though, as the use of multiple materials in PBF-LB/M is not broadly available. However, the different states of material in PBF-LB/M, i.e. bulk and powder material, provide the opportunity to create thermal metamaterials with locally varied thermal conductivities. To enable part design utilizing the bulk material as well as enclosed powder, this study investigates the respective thermal conductivities of Ti-6Al-4V. An experimental investigation of bulk and powder material at room temperature is carried out via the Modified Transient Plane Source (MTPS) method. The results are compared to those of earlier investigations to quantify variances due to measuring techniques. While the MTPS results are slightly lower than existent experimental values, the method is still deemed suitable for measuring thermal conductivities, especially for powders. For complete assessment of the powder material, because of the many uncertainties due to the particle size distribution and powder application, a computational model following the network modeling approach is created. The model is used to create a data set of 60 different powder bed configurations, which is then statistically evaluated to provide a description independent from powder packing. Finally, the application of the investigations to achieve thermal metamaterials capable of local temperature management with a single material is presented in a numerical study. Here, the use cases of thermal shielding as well as the concentration of heat flow is demonstrated.